1981
DOI: 10.1136/thx.36.11.842
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity and lung function in schoolchildren aged 7 to 11 years in South Wales and the West of England.

Abstract: The present study tests the suggestion that the respiratory morbidity of children resident in South Wales is substantially higher than that among children resident in some were matched for population density (with the assistance of the 1971 Census County Reports), socioeconomic index, and size with five schools in the Vale of Glamorgan (two small schools in the Vale were matched with one in Avon). In total 21 schools were selected. SUBJECTS Almost all the schools had mixed ability classes. In such schools wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In Britain there has been a marked increase in the rate of general practice consultations' and hospital admissions for childhood asthma, 23 although earlier suggestions that asthma mortality is increasing in childhood4 have not been substantiated. 35 The increase in medical activity may reflect changes in the prevalence or severity of the disease.…”
mentioning
confidence: 99%
“…In Britain there has been a marked increase in the rate of general practice consultations' and hospital admissions for childhood asthma, 23 although earlier suggestions that asthma mortality is increasing in childhood4 have not been substantiated. 35 The increase in medical activity may reflect changes in the prevalence or severity of the disease.…”
mentioning
confidence: 99%
“…A complete description of the study sample, questionnaire, and clinical measurements is to be found in the accompanying paper. 4 All values for the lung function indices forced expiratory volume in 0 75 second (FEVo.75) and forced vital capacity were adjusted for height (to a standard height of 130 cm) as described previously. 4 Adjusted values have analyses does not tally exactly with the number in the tables because regression analysis was only performed with the set of subjects for whom there was information recorded on all the independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…4 All values for the lung function indices forced expiratory volume in 0 75 second (FEVo.75) and forced vital capacity were adjusted for height (to a standard height of 130 cm) as described previously. 4 Adjusted values have been termed FEVo.751 and FVC I respectively. Multiple regression analysis was performed separately on the three dependent variables FEVo.751,FVC I, and FEVo.75 FVC ratio.…”
Section: Methodsmentioning
confidence: 99%